The relationship of instructional Leadership, Teachers’ Organizational Commitment And Students’ Achievement In Small Schools - Ponnusamy, Premavathy (2010)

(untitled)
Kepimpinan guru besar dikatakan sebagai faktor utama yang menyokong prestasi guru dari segi komitmen organisasi dan pencapaian pelajar.